Citywide Inclusive Water Supply : Role of Supplementary Urban Water Service Providers - Misra, Smita; Kingdom, Bill (World Bank, Washington, DC, 2022)
This report outlines a proactive vision of how development of the supplementary service provider in the water sector can promote citywide inclusive water supply, ensure rapid progress is made in achieving SDG 6.1, and deliver on the green, resilient, and inclusive development and jobs development agenda. Using case studies from around the world, it analyzes the potential of off-utility provision of water and develops a framework focused on what is needed to formalize, professionalize, and scale up these services. It also presents potential models for high-quality supplementary service provider water delivery and outlines how these can be implemented.